2022
DOI: 10.1002/admt.202200106
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity, Broad Working Range, Comfortable, and Biofriendly Wearable Strain Sensor for Electronic Skin

Abstract: coupled with an ultrabroad measuring range (2800%). Notwithstanding, the corresponding gauge factor (GF, known as the sensor sensitivity metric, GF = ΔR/R 0 ε, where ΔR denotes the change in resistance during stretching, R 0 represents the resistance before stretching, and strain is represented by ε.) is ≈16.9, indicating that the sensitivity of the sensor is poor and it may not be able to detect small strains. [18] Alternatively, inspired by the microcracks on the surface of spider legs, Robert et al. prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The sensors achieved great air permeability (80 mm s −1 ), impressive stretchability (GF = 520), and a wide operating range (up to 500% strain). 225 Wang et al reported a breathable strain sensor based on carbonized silk fabrics. The original silk fabric was carbonized by heat treatment under an inert atmosphere and then further encapsulated (Fig.…”
Section: Soft Electronic Applicationsmentioning
confidence: 99%
“…The sensors achieved great air permeability (80 mm s −1 ), impressive stretchability (GF = 520), and a wide operating range (up to 500% strain). 225 Wang et al reported a breathable strain sensor based on carbonized silk fabrics. The original silk fabric was carbonized by heat treatment under an inert atmosphere and then further encapsulated (Fig.…”
Section: Soft Electronic Applicationsmentioning
confidence: 99%
“…The progress in wearable sensor technology owes much to the evolution of flexible electronic devices. Among these, strain sensors stand out for their lightweight, remarkable sensitivity, and stretchability, making them ideal for easy attachment to human skin to capture electrical signals originating from human activities. To accomplish this, for conventional strain sensors, conductive fillers like carbon nanotubes, graphene, and polyaniline are incorporated into flexible substrate materials. However, the mismatched modulus between rigid conductive fillers and soft elastic substrates often results in reduced transparency and is prone to interface delamination, leading to decreased durability. To address these challenges, ionic conductive sensors have emerged as a promising substitute for electronic conductive sensors in recent times, including ionic hydrogels and ionogels. , Nevertheless, the mechanical performance deterioration and stability issues caused by the freezing and drying of ionic hydrogels have not been effectively resolved. In contrast, ionogels inherit the characteristics of ionic liquids, such as high-temperature stability and freeze resistance, making them ideal alternatives for hydrogels. Furthermore, the intrinsic humidity and temperature sensitivity of ionic liquids also confer multifunctionality to ionogels, enabling them to possess strain-sensing, temperature-monitoring, and humidity-detection capabilities. …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many recent studies focus on enhancing their sensitivity and stretchability to have a wider working range. [11][12][13][14] However, as their working range is extended, nonlinearity, which is one of the fundamental drawbacks of resistive sensors, becomes increasingly severe. 15 The linearity of a strain sensor refers to the positive correlation between the output signal and the applied strain.…”
Section: Introductionmentioning
confidence: 99%